Cultural Adaptation and Academic Success: Exploring the Experiences of Indonesian Students in Malaysian Universities - Handrianto, Ciptro; Solfema, Solfema; Jusoh, Ahmad Jazimin (Journal of Ethnic and Cultural Studies, 2025)
Higher education institutions are increasingly globalized, necessitating a deeper understanding of international students' adaptation processes. This study explores Indonesian students' cultural adaptation and academic success in Malaysian universities, considering the interplay of sociocultural, psychological, and academic dimensions. This study employs a quantitative approach using Structural Equation Modeling (SEM) to analyze survey responses from 347 Indonesian students across 12 Malaysian universities. Findings indicate that while Indonesian students generally adapt socioculturally, academic adaptation poses significant challenges, particularly regarding classroom participation, critical thinking expectations, and assessment methods. Institutional support, social networks, and language proficiency emerged as key mediators influencing academic success. Compared to previous studies on international students in Western contexts, this research highlights how cultural proximity does not necessarily equate to seamless academic integration. The study’s unique contribution lies in its focus on a specific yet underexplored student group, offering empirical insights for policymakers and university administrators to design culturally responsive academic support programs. The findings suggest that targeted interventions, such as language support and culturally adaptive teaching methods, can enhance Indonesian students' academic experiences in Malaysia. Future research should explore qualitative perspectives to deepen understanding and examine adaptation experiences across different fields of study.